Characterization of Astrocaryum macrocalyx Kernel fat - G. Lognay; A. Desmedt; K. Mejia; E. Trevejo; M. Marlier (Grasas y Aceites, 1995)
In the present work we investigated the glyceride and sterol compositions of Astrocaryum macrocalyx ("huicungo") kernel fat. This species is native from the Peruvian Amazonia (Iquitos). Gas chromatographic analysis of the fatty acids revealed 8 components, among which lauric (54.5%) and myristic (21.9%) acids predominate. The sterol profile is classic; β-sitosterol and campesterol are the main constituents (74.3 and 12.0% respectively) while the Δ7-sterols were detected in minute amounts. X-ray diffraction measurements showed that Astrocaryum macrocalyx kernel fat is stabilized in the β1'-2 polymorphic form at ambiant temperature.